NEW DATA ON SILICIFIED MICROFOSSILS FROM THE SATKA FORMATION OF THE LOWER RIPHEAN STRATOTYPE, THE URALS - Sergeev V.N.; Seong-Joo L. (My University, 2004)
Silicified microfossils found in the Satka Formation of the Burzyan Group (Lower Riphean stratotype of the southern Urals) are described. The research carried out augments the database on taxonomic composition of relevant microbiota. Besides cyanobacterial remains formerly known from that formation, abundant silicified microfossils representing eukaryotic microorganisms of phytoplankton are found. Representatives of these microorganisms occurring in a form of organic-walled remains in shaly siliciclastic rocks of the Satka and overlying Bakal formations have never been reported from cherty-carbonate successions of the Lower Riphean. In addition, the taxonomic composition of silicified cyanobacterial remains from the Satka Formation has been revised with due account for the current classification of fossil blue-green algae. The new finds and taxonomic correction of known forms elucidate further the microphytological characterization of the Lower Riphean and are important for biostratigraphic correlation of Precambrian deposits and for resolution of relevant problems. Described in the work are 15 species of 13 genera, the new form Corymbococcus rexii sp. nov. included.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей